ANTARA KEADILAN DAN KEPASTIAN HUKUM: KONFLIK YUDISIAL MAHKAMAH AGUNG –MAHKAMAH KONSTITUSI (STUDI KASUS PENINJAUAN KEMBALI) - Cindy Cherya (President University, 2018)
Although the positions of the Supreme Court and the Constitutional Court are parallel as stipulated in Article 24 paragraph (2) of the 1945 Constitution, these two institutions are still limited by different demarcation lines of authority. However, on a practical level, there are often conflicts between the boundaries of their relationship and authority, for example related to judicial review. This polemic stems from the Constitutional Court Decision Number 34/PUU-XI/2013 which in its decision annulled “Article 268 paragraph (3) of Criminal Procedure Code. As for Article 268 paragraph (3):